Respuesta :

xRoyce

First answer: -2

Second answer: 5

Answer:

(-2,5)

x= -2

y=5

Step-by-step explanation:

I'm going to solve this through substitution

We need a variable by itself (and we also need it to be positive)

We solve for y in the second equation

5x-y= -15

5x+15=y

We can then plug this in for y into the first equation

3x+2(5x+15)=4

and solve for x

3x+10x+30=4

13x= -26

x= -2

We can then plug this value in for x into any of the two beginning equations and solve for y

5(-2)-y= -15

-10-y= -15

-y= -5

y =5